ChemInform Abstract: Synthesis and Biological Properties of Multivalent Iminosugars. Issue 34 (August 2015) - Zelli, Renaud; Longevial, Jean‐Francois; Dumy, Pascal; Marra, Alberto
Abstract Review: [89 refs.